Imaging Curriculum of Complications in Orthotopic Liver Transplantation - Puneet Bhargava; Adeel Seyal; Mariam Moshiri; Chandana Lall; Sadaf Zaidi; Lorenzo Mannelli; Andre Dick; Sandeep Vaidya; Orpheus Kolokythas; Manjiri Dighe (Association of American Medical Colleges, 2013)
Abstract Introduction Orthotopic liver transplantation is an established treatment for patients with end-stage liver disease or acute liver failure. The procedure is distinct from living related liver transplantation with regard to surgical technique, postoperative anatomy, and some complications. The aim of this imaging curriculum is to educate radiology, surgery, gastroenterology, hepatology, and internal medicine trainees regarding basic anatomy of the post-orthotopic transplant liver, its various complications, and the role of imaging in their diagnosis. Methods This presentation provides an opportunity to learn imaging characteristics of complications of orthotopic liver transplantation in an interactive format. We have included relevant information and highlighted important teaching points in a series of PowerPoint presentations. This presentation is given to our incoming radiology residents to familiarize them with various aspects of imaging of orthotopic liver transplantation. Results Another version of this presentation has been presented in the University of Washington Annual Radiology Review Course for the last 3 years with excellent feedback. Discussion This resource has been designed to focus on imaging findings and includes a brief description of clinical information. Laboratory data and its details are not included as the focus of this resource is on understanding imaging findings. Adding more cases in quiz format at the end of the presentation will help reinforce learning.